PENGGUNAAN PENDEKATAN KETERAMPILAN PROSES DALAM PEMBELAJARAN PERKEMBANGAN PESERTA DIDIK UNTUK MENGINGKATKAN HASIL BELAJAR MAHASISWA PRODI BAHASA INGGRISSEMESTER IIC FKIP – UNMAS DENPASAR TAHUN AKADEMIK 2012/2013 - Putu Sri Astuti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2014)
This research is motivated by: (1) low student achievement; (2) low activity of student learning; (3) learning methodless attractive, making it less motivating for studentstolearn; (4) the students sometimes difficult to understandand developa concept that they never experienced directly. The purpose of this research is to improve student achievement using process skills approach and improve students learning activities through processs kills approach. Subjects were students of second semester C English Education Study Program Guidance and Counseling Unmas Denpasar with 40 students. Data collection method used is an essay test to determine student achievement. Data were analyzed with descriptive statistical analysis methods. The research method used was action research as much as 2 cycles. Each cycle with the basic steps: planning, acting, observing, reflecting, with arevised actionis always used to find a better and accurate results. The analysis shows an increasing in learning outcomes of second semester C English Study Program FKIP Unmas Denpasar students with the initial mean 1,97 which is in low catagory, the first cycle is 2,45 in the medium catagory, and 3,125 point at the second cycle which is in high catagory, and the student learning activities with the subject of development of students are also increasing. Therefore in this class action research, process skills approach is proven that it can incrases the students learning achievment.